Effect of Age on the Protein Profile of Healthy Malay Adults and its Association with Cognitive Function Competency - Bakar Z.H.A.; Damanhuri H.A.; Makpol S.; Kamaruddin W.M.A.W.; Sani N.F.A.; Hamzah A.I.Z.A.; Rani M.D.M.; Razali R.; Mazlan M.; Hamid H.A.; Mohamad M.; Ngah W.Z.W.; et al. (IOS Press, 2024)
Indexed by WOS/Scopus/ERA